EFFECTIVE TEACHER-LEARNER COMMUNICATION AND INTERACTION - A BRIEF LITERATURE REVIEW - Adrian NĂZNEAN (National Centre for Policy and Evaluation in Education, 2022)
Teaching is a social activity with a formative impact on learners, an activity in which communication plays a pivotal role. To aid the delivery of the information, a teacher can rely on both verbal and non-verbal elements. These are useful tools to provide feedback to the students and some can be used in a virtual teaching and learning environment. While distance education may have various limits in ensuring effective communication between the learners and their instructor, there are ways of combating the lack of elements that can lead to ineffective communication. Our mixed methodbased literature review will try to identify the ways in which successful and constructive communication can be established between the learners and the teachers.